2020
DOI: 10.46619/ijcmi.2020.1027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupressure on Constipation: A Systematical Review

Abstract: IntroductionConstipation is an important symptom among the functional disorders of the gastrointestinal tract. Pharmacological and non-pharmacological interventions are used to prevent constipation. One of the nonpharmacological methods used on constipation is acupressure. This systematic review aimed to examine the published studies on relieving constipation problem, to systematically review the data obtained in these studies, and to assess the effectiveness of acupressure on patients experiencing constipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…(10) Acupressure therapy has been shown to have a positive impact in treating constipation in patients during treatment. (6)(7)(8) This acupressure therapy can identify disorders or diseases in certain areas of the body by detecting the areas of the feet and hands. This therapy originates from China and ancient Egypt and was introduced to the West in 1920 by Dr William Fi gerald, an ENT specialist from America who together with his colleague Eunice Ingham mapped sensitive areas on the feet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(10) Acupressure therapy has been shown to have a positive impact in treating constipation in patients during treatment. (6)(7)(8) This acupressure therapy can identify disorders or diseases in certain areas of the body by detecting the areas of the feet and hands. This therapy originates from China and ancient Egypt and was introduced to the West in 1920 by Dr William Fi gerald, an ENT specialist from America who together with his colleague Eunice Ingham mapped sensitive areas on the feet.…”
Section: Discussionmentioning
confidence: 99%
“…Research that has been conducted to prove the benefits of this zone therapy has repeatedly shown that acupressure therapy has a positive effect on quality of life, stress, anxiety and reduction in pain. (7) Literature reveals that acupressure therapy is also very useful for cancer treatment, treating pain and fatigue. (16) Acupressure zone therapy increases blood flow to the appropriate organ or targeted body part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Acupressure can balance the energy, so it has beneficial effects according to the acupressure point. 13 Several studies were conducted that revealed the beneficial effect of acupressure on the constipation of patients. A systematic review conducted on patients with leukemia revealed that acupressure had positive effects on constipation.…”
Section: Introductionmentioning
confidence: 99%